Metabolic syndrome is a predictor of all site and liver-specific recurrence following primary resection of colorectal cancer: Prospective cohort study of 1006 patients. Issue 7 (July 2021) - Bhome, Rahul; Peppa, Nadia; Karar, Shoura; McDonnell, Declan; Mirnezami, Alex; Hamady, Zaed
Abstract: Introduction: Large epidemiological studies have demonstrated the link between metabolic syndrome and cancer development, including colorectal cancer. However, the influence of metabolic syndrome on disease progression is less well studied, particularly in the post-surgical setting. This study investigates the effect of metabolic syndrome on colorectal cancer recurrence (all-site and liver-specific) after curative surgery for Stage I-III disease. Materials and methods: Consecutive patients who underwent curative resection for Stage I-III colorectal cancer in a single UK centre were prospectively recruited. Disease-free and overall survival with metabolic syndrome as a factor, were determined using the Kaplan-Meier technique. Hazard ratios for all-site and liver-specific recurrence were determined using univariable and multivariable Cox-regression models. Results: 1006 patients were recruited and followed up for a median of 50 months (IQR 30–67). 177 patients (17.6%) met the criteria for metabolic syndrome. 245 patients (25.4%) developed recurrence, 161 (16.0%) of these had liver recurrence. The presence of metabolic syndrome was associated with a reduction in disease-free survival from 69 to 58 months ( p < 0.001) and overall survival from 74 to 61 months ( p < 0.001). Metabolic syndrome was an independent predictor of all-site (HR 1.76; p < 0.001) and liver-specific (HR 1.74; p = 0.01) recurrence. Conclusion: Metabolic syndrome is a predictor of all-site and liver-specific recurrence after primary resection of stage I-III colorectal cancer.